KINERJA PELAKSANAAN KEGIATAN DINAS PARIWISATA KABUPATEN BADUNG - A. A. Sagung Ayu Srikandi Putri (Forum Manajemen STIMI Handayani Denpasar, 2012)
Decentralization on the basis of Law No. 32 of 2004 on Local Governmentwhich local governments are given discretion to manage their own household, sothe area has the authority and discretion in implementing policies in accordancewith the aspirations of the community. Governance and service area is based on theprinciples of transparency, participation and accountabilityIn this regard, this paper aims to determine the performance of the implementationof activities seen from the input, output and outcome and performance accountabilityBadung Tourism Ofﬁ ce.The result of the implementation of Badung Tourism Ofﬁ ce in 2008 are in accordancewith the plan, and 8 ( eight ) exceeded the target performance level indicators and8 ( eight ), an indicator similar to the target, the average level of achievementgoals through the formulation of indicators and targets at 116 percent of averageachievement levels of activity amounted to 102.64 percent.